Dementia Pugilistica revisited - Castellani, R. J.; Perry, G. (Journal of Alzheimer's Disease, 2020)
Extensive exposure of boxers to neurotrauma in the early 20th century led to the so-called punch drunk syndrome, which was formally recognized in the medical literature in 1928. "Punch drunk" terminology was replaced by the less derisive `dementia pugilistica` in 1937. In the early case material, the diagnosis of dementia pugilistica required neurological deficits, including slurring dysarthria, ataxia, pyramidal signs, extrapyramidal signs, memory impairment, and personality changes, although the specific clinical substrate has assumed lesser importance in recent years with a shift in focus on molecular pathogenesis. The postmortem neuropathology of dementia pugilistica has also evolved substantially over the past 90 years, from suspected concussion-related hemorrhages to diverse structural and neurofibrillary changes to geographic tauopathy. Progressive neurodegenerative tauopathy is among the prevailing theories for disease pathogenesis currently, although this may be overly simplistic. Careful examination of historical cases reveals both misdiagnoses and a likelihood that dementia pugilistica at that time was caused by cumulative structural brain injury. More recent neuropathological studies indicate subclinical and possibly static tauopathy in some athletes and non- athletes. Indeed, it is unclear from the literature whether retired boxers reach the inflection point that tends toward progressive neurodegeneration in the manner of Alzheimer`s disease due to boxing. Even among historical cases with extreme levels of exposure, progressive disease was exceptional.